A multiscale crystal plasticity-multistage fatigue coupling framework for prediction of low-cycle fatigue life in laser additively manufactured titanium alloy - Ning Guo; Jiang Yu; Qingjun Zhou; Jilai Wang; Guangchun Xiao; Bingtao Tang; Zhongguo Zhang (Virtual and Physical Prototyping)
Existing aerospace fatigue life models inadequately predict high-strain cycle failures in TC11 titanium alloys due to overlooked dynamic microstructural evolution and multiscale damage, undermining critical airframe safety assessments. This study introduces a novel multiscale framework that synergistically integrates microstructure-sensitive crystal plasticity (CP) with a multistage fatigue (MSF) model to accurately predict the low-cycle fatigue (LCF) life of TC11 alloy fabricated via laser powder-directed energy deposition (LP-DED). The CP-MSF model synergistically integrates microstructure deformation mechanisms and heterogeneous plasticity-induced damage evolution from CP analysis with MSF's multiscale variable transmission framework, establishing a holistic framework that quantitatively captures dynamic microstructure evolution, crack nucleation-propagation transitions, and scale-dependent damage interactions. The validity of the proposed framework was tested against strain-life curves, demonstrating a mean prediction error about 4.6% across a range of strain amplitudes (0.4%–1.2%). This study further elucidates the individual contributions of microstructure morphology, α lath size and micro-orientation to LCF lifetime. Notably, the presence of basketweave microstructure and coarse α laths significantly enhances LCF life, whereas the micro-orientation has less effect. Additionally, Schmid factor (SF) analyses and intragranular misorientation axes (IGMA) investigations identified Pyramidal I slip as the predominant deformation mechanism under cyclic loading.